2020
DOI: 10.1101/2020.06.01.127514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autophagy in T cells from aged donors is maintained by spermidine, and correlates with function and vaccine responses

Abstract: Older adults are at high risk for infectious diseases such as the recent and vaccination seems to be the only long-term solution to the pandemic. While most vaccines are less efficacious in older adults, little is known about the molecular mechanisms that underpin this. Autophagy, a major degradation pathway and one of the few processes known to prevent aging, is critical for the maintenance of immune memory in mice. Here, we show induction of autophagy is specifically induced in human vaccine-induced antigen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Addition of GC7 further decreased Puromycin incorporation, CDK1 and IFNγ expression but did not impact significantly on the abundance of TBET and IRF4 protein. Interestingly, although IFNγ production was affected by DFMO, as reported recently for CD8 T cells (Alsaleh et al, 2020) and DFMO+GC7, the protein was still detectable in all cells, which was in contrast to Eif5a/Dhps KO cells where a significant proportion of the population produced no detectable IFNγ (Fig 2B S1).…”
Section: Spermidine Availability Affects Some But Not All Eif5a-regulated Proteinssupporting
confidence: 77%
“…Addition of GC7 further decreased Puromycin incorporation, CDK1 and IFNγ expression but did not impact significantly on the abundance of TBET and IRF4 protein. Interestingly, although IFNγ production was affected by DFMO, as reported recently for CD8 T cells (Alsaleh et al, 2020) and DFMO+GC7, the protein was still detectable in all cells, which was in contrast to Eif5a/Dhps KO cells where a significant proportion of the population produced no detectable IFNγ (Fig 2B S1).…”
Section: Spermidine Availability Affects Some But Not All Eif5a-regulated Proteinssupporting
confidence: 77%
“…However, in our study, we found that lymphocyte loss was correlated with a decrease of secondary biliary salts in LVS patients, most likely associated with increased gut permeability that leads to bacterial translocation, as we observed increased circulating DNA for Micrococcaceae and Enterobacteriaceae family members. Moreover, the transformation of spermidine into N1, N8 diacetylspermidine was linked to decreased ALC, in accordance with the role of spermidine in preventing aging-related loss of lymphocyte fitness [ 36 38 ].…”
Section: Discussionmentioning
confidence: 76%
“…Another metabolic pathway pertaining to polyamines with high biological significance for age-related immunosenescence [ 36 38 ] was also strongly associated with the duration of RT-qPCR positivity, ALC, and disease severity (Fig. 5E–G and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For reasons that are not completely clear, hypusinated eIF5A appears to have a skewed impact on mitochondrial protein translation, with defective hypusination resulting in decreased oxidative phosphorylation in macrophages and T cells (Puleston et al, 2021; Puleston et al, 2019) and increased reliance on glucose in kidney cells (Cougnon et al, 2021; Melis et al, 2017). Furthermore, the mitochondrial programming induced by hypusinated eIF5A, with increased levels of autophagy, can protect cell function––reversing B cell senescence (Zhang et al, 2019a), promoting vaccine immunogenicity in the elderly (Alsaleh et al, 2020), and protecting the brain from premature aging as well as ischemic-related stress (Bourourou et al, 2021; Liang et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%